Pengalaman Konsumen, Nilai dan Keinginan untuk Berbelanja Ulang di Kantin Mahasiswa - Alhapen Ruslin Chandra (Politeknik Negeri Padang, 2020)
This study aims to explore the role of experience of students as consumers on utilitarian and hedonic values ​​towards intention to revisit canteen of students in Politeknik Negeri Padang. Consumer experience are measured using dimensions of sense, feel, think, act, and relate. Data were analysed using partial least square structural equation modelling (PLS-SEM). This study found that consumer experience from dimensions of sense, feel and act have a significant positive impact on utilitarian values. In addition, sense, and act also have a significant positive influence on hedonism value. Furthermore, utilitarian, and hedonic values ​​have a positive and significant impact towards intention to revisit the canteen. Thus, the utilitarian and hedonic values ​​obtained through consumer experience will increase student intention to revisit the canteen.